Fiscal Policy in an Endogenous Growth Model - Saint-Paul, G. (Quarterly Journal of Economics, 1992)
In a neoclassical growth model, it is possible to make a case for public debt, because a balanced growth path may be dynamically inefficient. This paper shows that this possibility no longer holds in an endogenous growth model with constant external returns to capital. It is shown that an increase in public debt reduces the growth rate, so there always exists a future generation that will be harmed, and that a reduction in public debt, although it increases the growth rate, cannot be Pareto-improving: one current generation must be harmed.